The language and reality of time - Sattig, Thomas (UK : Oxford university press, 2006)
Thomas Sattig develops a framework for doing philosophy of time and offers a three-dimensionalist picture of the material world. He brings together different perspectives, linking our ordinary conception of time with the physicist's conception, and linking this with questions on the philosophy of language.
Includes bibliographical references and index.
Keywords: Time; Electronic books